Analysis of Multi-Path Scheduling Network Model for Intelligent Transportation - Weiyang Qin (Dianxin kexue)
In the field of intelligent transportation, vehicle scheduling is a complex issue with multi-path, multi-types of vehicles and multi-destination. In this process, some time-varying attributes and dynamic indicators have a direct impact on the scheduling process and result. A scheduling network model, with multi-path, multi-types of vehicles, multi-destination and dynamic factors was proposed. The new modeling elements, virtual node and virtual path, were used for mathematical description and graphical expression of vehicle scheduling network model. Priority-based scheduling network was presented, and the validity of the model was verified.